Is it True that Oil Palm Plantations are the Main Driver of Indonesia’s Tropical Forest Deforestation? - Yanto Santosa; Arzyana Sunkar; Rozza Tri Kwatrina (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2020)
The extent to which oil palm has contributed to deforestation of primary forests is still an intensive debate in public space. Even though the term deforestation and the results of the study and study are still